2017
DOI: 10.1071/sr15377
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative response of soil organic carbon to 40 years of crop residue incorporation under contrasting nitrogen fertilisation regimes

Abstract: Abstract.Crop residue incorporation (RI) is recommended to increase soil organic carbon (SOC) stocks. However, the positive effect on SOC is often reported to be relatively low and alternative use of crop residues, e.g. as a bioenergy source, may be more climate smart. In this context, it is important to understand: (i) the response of SOC stocks to long-term crop residue incorporation; and (ii) the qualitative SOC change, in order to judge the sustainability of this measure. We investigated the effect of 40 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 55 publications
5
22
1
Order By: Relevance
“…Nitrogen fertilization, with or without P application, significantly increased SOC concentration (Table 1), in agreement with other findings (Smith et al 2015;Poeplau et al 2017). Applying P fertilizer had no consistent influence on SOC concentration.…”
Section: Resultssupporting
confidence: 91%
“…Nitrogen fertilization, with or without P application, significantly increased SOC concentration (Table 1), in agreement with other findings (Smith et al 2015;Poeplau et al 2017). Applying P fertilizer had no consistent influence on SOC concentration.…”
Section: Resultssupporting
confidence: 91%
“…Another treatment that has been the subject of multiple LTEs is the effect of mineral N fertilizer on C sequestration. Although generally no effect is observed (e.g., Nardi et al, 2004;Triberti et al, 2008;Poeplau et al, 2017), some authors report a small increase in SOC stocks after mineral N fertilization (Dersch and Böhm, 2001;Ladha et al, 2011). However, a potential increase in SOC stocks can be offset by the greenhouse gases produced during the manufacturing of mineral N fertilizer (Gao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As the addition of organic materials to soil channels the accumulation of extra carbon (Bharali et al 2017;Baruah and Baruah 2015;Kirkby et al 2013), SOC was found enhanced under T3, T5 and T6, i.e., under the inorganic fertilizer blended with organic materials. The increased SOC helps microbes to provide nutrients to plants by keeping carbon and nitrogen balanced in soil, otherwise microbes would decompose existing organic carbon of the soil (Fontaine et al 2004;Murphy et al 2015;Poeplau et al 2017). The SOC was found increased under inorganic T2 also, which might be due to the fact that the application of urea assimilated carbon by improving leaf, shoot and root biomasses of rice plants (Liu et al 2017;Ge et al 2016;Zhu et al 2018).…”
Section: Soil Propertiesmentioning
confidence: 99%